Analysis Hydromorphometric of Qandil River Baisn (Raparin Journal of Humanities (RJH), 2023)
The watershed of the Qandil River is located in the northeast of Sulaimani province and the east of the Kurdistan Region. Physio-graphically, the study area is considered to be a rugged mountainous area, astronomically located between the latitudes (36 13 14–36 31 15) north and the longitudes (44 53 52–45 06 13) east. The area of the watershed is (219 km2) The main objective of this study is to identify the environmental characteristics of the study area and draw specific maps for each of them in order to take the necessary steps to analyze the hydromorphometric area. At the beginning of the study, the natural environment of the watershed of the Qandil River and its effects on hydromorphometric factors such as (Geology, altitude, and climate were analyzed. This is by analyzing the characteristics of each of these genders and their effects at different levels at the level of water resources. In the second part, focused on each of the most important geomorphology and morphometry of watersheds of the Qandil river watershed, which consists of two watersheds. In the first topic, after preparing the map of the river irrigation network, the most important geomorphological features of the watersheds are discussed, such as main rivers, branches, irrigation systems, streams and their types. In the second topic, the most important morphometric measurements were doing for watersheds. On this topic, emphasis was placed on the study of their characteristics (area, shape, altitude, and river network). The results of the study show that the natural characteristics of the study area play a major role in the richness of water resources and the rapid flow of streams, tributaries, and the main river of the watershed.